2016
DOI: 10.1038/srep29621
|View full text |Cite
|
Sign up to set email alerts
|

Reduced TRMU expression increases the sensitivity of hair-cell-like HEI-OC-1 cells to neomycin damage in vitro

Abstract: Aminoglycosides are ototoxic to the cochlear hair cells, and mitochondrial dysfunction is one of the major mechanisms behind ototoxic drug-induced hair cell death. TRMU (tRNA 5-methylaminomethyl-2-thiouridylate methyltransferase) is a mitochondrial protein that participates in mitochondrial tRNA modifications, but the role of TRMU in aminoglycoside-induced ototoxicity remains to be elucidated. In this study, we took advantage of the HEI-OC-1 cell line to investigate the role of TRMU in aminoglycoside-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 51 publications
(63 reference statements)
1
42
0
Order By: Relevance
“…6a,c). Previous studies have reported that cleaved caspase-3 and TUNEL can be used as markers of apoptosis in aminoglycoside-induced HC death303233343536. To confirm our findings, we performed active caspase-3 and TUNEL staining to detect the apoptotic HEI-OC1 cells.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…6a,c). Previous studies have reported that cleaved caspase-3 and TUNEL can be used as markers of apoptosis in aminoglycoside-induced HC death303233343536. To confirm our findings, we performed active caspase-3 and TUNEL staining to detect the apoptotic HEI-OC1 cells.…”
Section: Resultssupporting
confidence: 76%
“…HEI-OC1 cells, a HC-like cell line, express several molecular markers of cochlear HCs, including calbindin, calmodulin, math1, myosin7a, and prestin28293031, and they are commonly used to study the protection of HCs. We used Myosin 7a as the HC marker, and immunostaining showed that all HEI-OC1 cells could be double labeled by Myosin 7a and c-Myb, demonstrating that c-Myb is expressed in HEI-OC1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that ROS is involved in aminoglycoside‐induced HC damage . The intracellular ROS level was increased after gentamicin treatment by DCFH‐DA staining compared with the untreated control in primary culture of cochlear HCs, but NAC inhibited the intracellular ROS level after gentamicin damage (Figure A).…”
Section: Resultsmentioning
confidence: 87%
“…Hearing loss is regarded as a very common sensory disorder in humans all over the world, which seriously affects the quality of human life. In most cases, hearing loss is mainly attributable to hair cell (HC) damage caused by ototoxic drugs, of which aminoglycoside antibiotics, including kanamycin, amikacin, neomycin and gentamicin, are such a typical kind of drugs, with the potential to elicit toxic reactions to structures of the inner ear . Although those drugs are widely used to treat gram‐negative bacterial infections, the ototoxic side effects have a great limitation in clinical use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation